Integrating Programmable Smart-NICs into Industrial Packet-Processing Systems - Blomkvist, Lina; Svensson, Tove (My University, 2021)
In order to cope with the requirements of 5G, Smart Network Interface Controllers are being used to offload general use CPUs. For them to be able to become more widely used, research of how to integrate them into already existing industrial systems and the cost of such a transition is needed. This thesis presents the method of integrating a P4 programmed Netronome Agilio Smart Network Interface Controller (SNIC) into a high speed industrial packet processing pipeline. A partition of the industrial system handling packet classification is translated and implemented and run on the SNIC and tested and compared to the original program performing the same task. The effect on performance is analysed and a qualitative evaluation of the process conducted. The challenges faced in this project consisted of understanding the industrial system environment and how to seamlessly translate the code without losing the original functionality.
Keywords: 5G; P4; SDN; SNIC